Pharmacokinetics of Rilpivirine and 24-Week Outcomes after Switching from Efavirenz in Virologically Suppressed HIV-1-Infected Adolescents. Issue 3 (April 2018) - Jantarabenjakul, Watsamon; Anugulruengkitt, Suvaporn; Kasipong, Naruporn; Thammajaruk, Narukjaporn; Sophonphan, Jiratchaya; Bunupuradah, Torsak; Cressey, Tim R; Colbers, Angela; Burger, David M; Phongsamart, Wanatpreeya; Puthanakit, Thanyawee; Pancharoen, Chitsanu; et al.
Background: Rilpivirine (RPV), a non-nucleoside reverse transcriptase inhibitor drug, could be a favourable drug for maintenance therapy in HIV-infected adolescents because it has few long-term side effects. However, data among adolescents switching from efavirenz (EFV) to RPV are limited. This study investigated the pharmacokinetics (PK), safety and efficacy of RPV in virologically suppressed HIV-1-infected adolescents after switching from EFV. Methods: Adolescents aged 12–18 years on EFV-based antiretroviral therapy (ART) were switched from EFV to RPV (25 mg, once daily). Intensive 24-h blood samplings at 0 (pre-dose), 1, 2, 4, 5, 6, 9, 12 and 24 h were performed 4 weeks after switching. PK parameters were calculated using a non-compartmental method and compared with published data from the PAINT and pooled ECHO/THRIVE substudies. HIV RNA level was measured at weeks 12 and 24. Biochemical profiles were measured at baseline and week 24. Results: From January to June 2016, 20 adolescents (12 male) were enrolled. Median (IQR) age was 16 (15–17) years and weight was 49 (42–59) kg. Mean (sd ) AUC24 h, C24 h and Cmax of RPV were 2, 041 (745) ngh/ml, 69 (29) ng/ml and 143 (65) ng/ml, respectively. Median (IQR) Tmax was 5 (2–9) h. Four adolescents had C24 h <40 ng/ml. All PK parameters were comparable with published data. All adolescents remained virologically suppressed at week 24. Significant decreases in fasting total cholesterol, triglyceride and low-density lipoprotein were observed ( P -value <0.05). Conclusions: Virologically suppressed HIV-infected adolescents had adequate RPV exposure and remained virologically suppressed after switching from EFV. RPV can be used as long-term maintenance ART in HIV-infected adolescents.